Multigeneration Effects of Plasma Irradiation to Seeds of Arabidopsis Thaliana and Zinnia on Their Growth. Issue 1723 (29th January 2015) - Sarinont, Thapanut; Amano, Takaaki; Koga, Kazunori; Shiratani, Masaharu; Hayashi, Nobuya
ABSTRACT: We have studied multigeneration effects of plasma irradiation to seeds of Arabidopsis thaliana (L.) and Zinnia peruviana (L.) on their growth using a scalable DBD device. Atmospheric plasma irradiation enhances growth of these plants in multi-generations. For Arabidopsis thaliana (L.) in the third generation, the leaf area is 2 times larger than that without plasma irradiation and the stem length is 1.5 times longer than that without plasma. For Zinnia peruviana (L.) in the second generation, the stem length is 2 times longer than that without plasma.